13y+14y-17y+17=10y+17. end!
2006-12-21 01:50:23
·
answer #1
·
answered by grassu a 3
·
1⤊
0⤋
13y - [-14y + {9y - (-8y + 17)}
First: solve this according to order of operations: PEMDAS >>>
>>> ( ), exponents, multiplication, division, addition, subtraction
= 13y - [-14y + {9 +8y - 17}
= 13y - [-14y + 9y + 8y - 17]
= 13y - [3y - 17]
= 13y - 3y + 17
= 10y + 17
2006-12-21 06:22:56
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
it 's 10y+17
first operate the expression within inner brackets and then the other brackets.
so it wud be 17y+17
now subtract 14y from this .17y-14y=3y
and finally....13y-3y+17=10y+17
2006-12-21 01:51:26
·
answer #3
·
answered by physics 2
·
1⤊
0⤋
13y-(-14y+(9y-(-8y+17) 13y(-14y+9y+8y+17) 13y-(3y+17) 13y-3y-17 10y-17 ,but if you want y it is y=17/10 so y=1.7
2006-12-21 02:18:24
·
answer #4
·
answered by the winner 1
·
1⤊
1⤋
10y+17
2006-12-21 01:56:01
·
answer #5
·
answered by ihavetheanswer 2
·
0⤊
1⤋
ohhhh i love these kinda math!!! :)
13y-{-14y+[9y-(-8y+17)]}
13y-[-14y+(9y+8y-17)]
13y-(-14y+9y+8y-17)
13y+14y-9y-8y+17
10y+17
:D
2006-12-21 01:55:26
·
answer #6
·
answered by CutePanda 2
·
1⤊
0⤋
13y-{-14y+[9y+8y-17]}
13y-{-14y+9y+8y-17}
13y-{3y-17}
13y-3y+17
10y+17
2006-12-21 01:50:20
·
answer #7
·
answered by ships 2
·
1⤊
0⤋
easy:
10y+17
2006-12-21 02:23:37
·
answer #8
·
answered by ~ ANGEL ~ 5
·
0⤊
1⤋
13y-{-14y+[9y-(-8y+17)]}
=13y-{-14y+[9y+8y-17]}
=13y-{-14y+17y-17}
=13y-3y+17
=10y+17
2006-12-21 01:52:19
·
answer #9
·
answered by pigley 4
·
1⤊
0⤋
13y-{-14y+[9y-(-8y+17)]}
=13y-{-14y+[17y-17]}
=27y-[17y-17]
=10y+17
2006-12-21 02:00:14
·
answer #10
·
answered by angad m 2
·
1⤊
0⤋